Metabolic syndrome in postmenopausal women - Yu.E. Dobrokhotova; Ilina I.Yu.; M.R. Narimanova; D.M. Ibragimova (РМЖ. Мать и дитя, 2018)
Metabolic syndrome in postmenopausal women Yu.E. Dobrokhotova, I.Yu. Il’ina, M.R. Narimanova, J.M. Ibragimova Pirogov Russian National Research Medical University, Moscow, Russian Federatin To date, cardiovascular diseases and metabolic syndrome occupy one of the leading places in structure of morbidity and mortality. It is known that an estrogen deficiency state adversely affects blood lipid spectrum, state of vessels and, consequently, condition and work of the heart and brain. Aim: to identify influence of menopausal hormone therapy (MHT) on course of the metabolic syndrome in postmenopausal women. Patients and Methods: 109 postmenopausal women, whose age ranged from 48 to 57 years (mean age 52.4±3.6 years), were examined. A period since the last menstruation was from 1 year to 5 years. Analysis of available complaints from the cardiovascular system, measurement of blood pressure (BP) and pulse were performed; laboratory tests (biochemical blood test, including a lipid profile, an estradiol level determination) and additional instrumental studies (electrocardiography (ECG), echocardiography (ECHO), veloergometry (VEM)) were carried out. Results: one or another pathological symptom from the cardiovascular system was detected in 64 patients (58.7%). Dependence of various manifestations of a pathological state of the cardiovascular system on the level of estrogens was revealed. Treatment was prescribed to patients who had changes in the lipid profile, as well as ECG, ECHO and VEM (n = 46). A drug containing estradiol 1 mg / drospirenone 2 mg (Angeliq®) was prescribed. A gestagenic component in this medication has antimineralocorticoid and antiandrogenic activity. The use of MHT for 6 months in most women allowed normalizing the level of blood pressure, lipid profile, improving some parameters of the ECG and ECHO. Conclusion: with the administration of MHT, containing drospirenone, a decrease in blood pressure is observed due to its diuretic effect. Also, the medication Angeliq® helps to prevent development of the metabolic syndrome, which ultimately reduces the mortality rate from its complications. Key words: metabolic syndrome, estrogen deficiency, arterial hypertension, atherosclerosis, diseases of the cardiovascular system, menopausal hormonal therapy, Angeliq®. For citation: Dobrokhotova Yu.E., Il’ina I.Yu., Narimanova M.R., Ibragimov J.M. Metabolic syndrome in postmenopausal women. Russian journal of Woman and Child Health. 2018;1(1):33–38.